2000
DOI: 10.1207/s15327914nc372_6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transportation and Delay in Processing on the Stability of Nutritional and Metabolic Biomarkers

Abstract: The effects of transportation and delay in processing of blood samples on the concentration of biomarkers are significant in epidemiological studies for which specimens are collected from participants at locations other than a designated center or laboratory. These sources of variability in measurement were studied by collecting two sets of blood samples from 51 men between 26 and 50 years of age. The first set was sent immediately to the laboratory for processing. The second set was transported by car for one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Examples of temperature-sensitive diagnostic analytes include red and white blood cells, high-density-lipoprotein cholesterol, glucose, creatinine, total cholesterol, total testosterone, free testosterone, alkaline phosphatase, total bilirubin, thiobarbituric acid-reactive substances [11], glucose and potassium [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Examples of temperature-sensitive diagnostic analytes include red and white blood cells, high-density-lipoprotein cholesterol, glucose, creatinine, total cholesterol, total testosterone, free testosterone, alkaline phosphatase, total bilirubin, thiobarbituric acid-reactive substances [11], glucose and potassium [12]. …”
Section: Discussionmentioning
confidence: 99%
“…An additional sample set, designed for the estimation of biological variation, consisted of serial samples from 17 volunteers (7 men and 10 women) obtained at 0, 1, and 4 weeks. All study specimens (79 total) were collected, processed, and stored with standardized procedures that we have described previously (30 ). The experimental protocols were approved by the Institutional Review Board at the University of Buffalo and informed, written consent was obtained from all participants.…”
Section: Materials and Methods Patients And Specimensmentioning
confidence: 99%
“…A recent analysis of the performance of a variety of clinical laboratory instruments and methods that measure glucose revealed that 41% of instruments have a significant bias from the reference method that would result in potential misclassification of >12% of patients (35). There are also potential preanalytic errors owing to sample handling and the well-recognized lability of glucose in the collection tube at room temperature (36,37). Even when whole blood samples are collected in sodium fluoride to inhibit in vitro glycolysis, storage at room temperature for as little as 1 to 4 h before analysis may result in decreases in glucose levels by 3–10 mg/dl in nondiabetic individuals (3639).…”
Section: Can the A1c Test Be Used To Diagnose Diabetes?mentioning
confidence: 99%